Directive and Expresive Speech Act in Intagram Account of Tegalan Languange Waduke_njeblug as The Variety of Local Language - Khotimah, Khusnul; Rohmadi, Muhammad (Cakrawala: Jurnal Pendidikan, 2022)
This study aims to describe directive and expressive speech acts that appear in the reservoir_njeblug Instagram account. The benefit of this research is to increase the diversity of language knowledge typical of the Tegal dialect "ngapak" which contains directive and expressive speech. The research method used is descriptive qualitative in the form of text posted on social media Instagram reservoir_njeblug account. The results of the study in the form of directive and expressive speech acts amounted to 54 data collected for two months, namely January and February 2022, there were 26 directive functions and 28 expressive functions with the percentage of directives prohibiting 5.56%, warning 20.37%, suggesting 14.81%, inviting 5.56% and ordering 1.85%. Expressive function surrender 25.93%, pity 1.85%, disappointed 16.67%, satire 3.70%, concern 1.85% and criticize 1.85%. Posts with an expressive function of surrender can be seen from the data that the intensity is most often posted because the account seeks to invite readers to together see the real reality of life and to always be grateful and surrender to what has been outlined in their life.